If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -2 + -7p = -5 + p + -4p Reorder the terms: -2 + 3p + -7p = -5 + p + -4p Combine like terms: 3p + -7p = -4p -2 + -4p = -5 + p + -4p Combine like terms: p + -4p = -3p -2 + -4p = -5 + -3p Solving -2 + -4p = -5 + -3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3p' to each side of the equation. -2 + -4p + 3p = -5 + -3p + 3p Combine like terms: -4p + 3p = -1p -2 + -1p = -5 + -3p + 3p Combine like terms: -3p + 3p = 0 -2 + -1p = -5 + 0 -2 + -1p = -5 Add '2' to each side of the equation. -2 + 2 + -1p = -5 + 2 Combine like terms: -2 + 2 = 0 0 + -1p = -5 + 2 -1p = -5 + 2 Combine like terms: -5 + 2 = -3 -1p = -3 Divide each side by '-1'. p = 3 Simplifying p = 3
| 3x^2*8x^5= | | n-3=-4n-(n-3) | | 2y-3y+-1=4 | | -7(3r-4)=-20+9r | | 28-13.8x=-54.8 | | 4s-12*(s-2)=s | | 20z+3z-21z-1=13 | | -78=6U+12 | | 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) | | 50+5x=15+12x | | 12x-5=4x-1 | | 7x+11=7+7x |